2023
DOI: 10.3390/vaccines11010140
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Premature Ovarian Insufficiency after Human Papilloma Virus Vaccination: A PRISMA Systematic Review and Meta-Analysis of Current Evidence

Abstract: (1) Background: Premature ovarian insufficiency (POI) has been linked to human papilloma virus (HPV) vaccination in small case-reports. The aim of this meta-analysis was to evaluate the risk of POI after HPV vaccination. (2) Methods: Electronic searches in MEDLINE Scopus, LILACS, ClinicalTrials.gov, EMBASE, PROSPERO, Cochrane CENTRAL and other registries were searched from inception to September 2022. Inclusion criteria were cohort studies of female children or adolescents vaccinated with quadrivalent (4vHPV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although POI following HPV vaccination has been reported in a few cases [35], a meta-analysis revealed that there was no significant risk of the disease in quadrivalent, bivalent, or 9-valent vaccinated patients compared to that in unvaccinated controls [36].…”
Section: Human Papilloma Virus (Hpv) Vaccinationmentioning
confidence: 94%
“…Although POI following HPV vaccination has been reported in a few cases [35], a meta-analysis revealed that there was no significant risk of the disease in quadrivalent, bivalent, or 9-valent vaccinated patients compared to that in unvaccinated controls [36].…”
Section: Human Papilloma Virus (Hpv) Vaccinationmentioning
confidence: 94%